2011
DOI: 10.1016/j.compositesa.2010.10.012
|View full text |Cite
|
Sign up to set email alerts
|

A modified Arcan test to analyze the behavior of composites and their assemblies under out-of-plane loadings

Abstract: Composite materials are a key element in weight reduction strategies, so the analysis of the mechanical behavior of assemblies of composite modules is of great importance. Failure initiation in bonded assemblies involving composites is often associated with crack initiation in the adhesive or delamination of the composite plies close to the adhesive joint, caused by interlaminar or throughthickness stresses. Thus, the analysis of the behavior of composites and their assemblies under outof-plane loadings is nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…One of the most important problems is the specimen-fixture connection which causes bending or unwanted third mode loading conditions ( Figure 1). This problem had been mentioned by Hosseini et al (2008), Cognard et al (2011. In this research, in order to obtain reliable results of fracture parameters, correction factors of new designed fixture and modified Arcan fixture were determined using three-dimensional finite element analysis.…”
mentioning
confidence: 99%
“…One of the most important problems is the specimen-fixture connection which causes bending or unwanted third mode loading conditions ( Figure 1). This problem had been mentioned by Hosseini et al (2008), Cognard et al (2011. In this research, in order to obtain reliable results of fracture parameters, correction factors of new designed fixture and modified Arcan fixture were determined using three-dimensional finite element analysis.…”
mentioning
confidence: 99%
“…Consequently, both the specimen geometry and the set fixation must be optimized in order to reduce these stress concentration. The current specimen geometry used in this study has been proposed by Cognard et al [17] and avoids the stress concentration in order to obtain reliable results (thanks to the grooves machined in the specimen see Fig. 1(c)).…”
Section: Materials and Experimental Setupmentioning
confidence: 99%
“…It is based on the use of specimen manufactured from thin composite plates bonded to metallic substrates. It has already been shown that this method allows us to obtain reliable results [17]. In these previous works, the results were presented in terms of macroscopic failure envelope of the laminates.…”
Section: Introductionmentioning
confidence: 98%
“…Different modes are obtained with different loading angles, using a tensile testing machine. Along the years, many researchers have used Arcan's original or modified specimen [63,5,65,55,28,32]. Driemeier et al [31] proposed a modified Arcan specimen that can be tested at high or low triaxialities, depending the direction the specimen is loaded.…”
Section: Accepted Manuscriptmentioning
confidence: 99%